Nostalgia, Recursivity, and the Re-Performance of Structural Film - Whitworth, Christian (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2022)
In the fall of 2010, contemporary artist Kerry Tribe staged a live re-performance of Hollis Frampton’s 1971 structural film Critical Mass, signaling a recent wave of nostalgic returns to cinema’s past in search of alternative technologies, methodologies, and exhibition structures. This essay reads Tribe’s re-performance alongside George Landow’s 1999 parody of Frampton’s original to reconsider a temporal tension between the historical longing of nostalgia and the futurity of intermedial recursivity. Together, these “films” determine a process of spectatorial subject formation proper to cinema’s changing specificity, resulting in a constant tension between the reception and re-performance of cinema as a set of continuous yet distributed desires, as a feeling of nostalgia for an event which has yet to recur.